Sedimentation Characteristics and Sediment Transport in the Palu River Estuary - Sucipto, Adi; Thaha, M. Arsyad; Hatta, M. Putra; Mahmuddin, Faisal (Salehan Institute of Higher Education, 2025)
Sedimentation is the process through which materials transported by water flow settle within that water. Changes in current patterns, driven by tides and variations in current velocity, can influence sediment transport. This study aimed to identify sediment transport patterns and analyze the characteristics of suspended sediment and bed load in the Palu River estuary. We employed field investigations, two-dimensional (2D) numerical modeling, and data analysis to process the findings. The results indicated that the sediment characteristics in the Palu River estuary varied, with a predominance of sand and gravelly sand. Additionally, sediment transportation patterns were found to be primarily influenced by river flow discharge rather than tidal effects. The research findings are presented in a correlation equation that illustrates the relationship between dimensionless parameters: C = ρs.(a.ψ)bwith coefficient values of a = 412.71 and b = (-0.545). The results of this correlation equation indicate that as the energy from water movement increases, sediment becomes more dispersed, leading to changes in the concentration of sediment particles. It can be concluded that various variables affect sediment transport due to hydrodynamic conditions. Doi: 10.28991/CEJ-2025-011-02-03 Full Text: PDF